VERBA DALAM KALIMAT PASIF BAHASA JEPANG - Lina Rosliana (Universitas Diponegoro, 2014)
Abstract Verb, is an important element to build a sentence in every language, including Indonesian and Japanese. When we make a complete sentence in Japanese, we use verb as a marker of activity or situation. Like every kind of verb in every language in this world, Japanese verb shows its uniqueness, if we see from the form, the function, or the meaning of it. Verb in Japanese passive voice is marked by –rareru or –reru (V-rareru or V-reru) conjugation that comes in the end of the verb. It stands as a bound morpheme and has a grammatical meaning. Key words: Japanese, verb, passive voice, conjugation